Mekanisme Penyusunan Laporan Pertanggungjawaban Anggaran Pendapatan dan Belanja Daerah - Putu Gede Satya Wiguna; I Gusti Bagus Suryawan; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2024)
The central government gives authority to regional governments to take care of their household affairs which are unique to the region with the aim that local governments are more effective in managing regional affairs both in terms of development, utilization and management of natural resources and human resources. The Regional Head who plans the APBD to organize his administration is also required to be able to provide accountability/provide reports on the results of the use of the APBD. The use of this APBD, of course, must have an agency that oversees it, in the administration of regional government that supervises it, namely the DPRD. Based on this description, the problems examined in this study are: What is the mechanism for preparing the APBD accountability report? according to Law Number 17 of 2003 is a regional financial plan approved by the Regional People's Representative Council (DPRD). This research is a normative research that uses a statutory approach. The legal material used in this study comes from the results of library research which consists of primary and secondary legal materials obtained through literature review techniques supported by analytical techniques. From the results of this study it can be interpreted that accountability and oversight are one unit to realize good governance, because it can provide an evaluation of the performance of the government for the future.